Making the Case for Play in Academic Libraries - Bradley-Ridout, Glyneva (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2026)
Academic libraries are evolving beyond their traditional role as centers for study and research. With growing concern over student stress, burnout, and wellbeing, libraries have an opportunity to support student success through creative means, including play. Play is often misunderstood and undervalued in adulthood, yet research shows it offers profound benefits. This perspective piece argues that academic libraries are uniquely positioned to offer students the opportunity and permission to engage in play, and that play has benefits to existing academic library spaces. Presenting three arguments examining the benefits of play in adulthood, for post-secondary students, and in academic libraries, this article advocates that play is a natural extension to the work being done to support students in academic library spaces.